MORAL VALUE AND CHARACTERS BUILDING EXPOSED IN FOLKLORE OF TONGKAT TUNGGAL PANALUAN - Nadeak, Lasmaida; Simbolon, Masliana; Sihotang, Rani Yanti; Sembiring, Yenita Br (Universitas Pendidikan Ganesha, 2020)
Folklore is a traditional story and plays an important role in teaching character of children because it is full of moral values. Folklore become a guide lines and also become a role model to behave well because in folklore there is an implied meaning containing advices and moral messages. The purpose of this study is to find out the moral values of folklore Tongkat Tunggal Panaluan and the importance of those values to build good character of children. This study is qualitative research design and data was collected from reading the folktale text repeatedly and then analyzed the data with content analysis. The instruments of this research are interview and documentation. The result of this study showed that there are four dominant values contain in folklore Tongkat Tunggal Panaluan include religious value, honesty value, responsibility value and social value that divided into two, helping each other and caring each other. From the research, the researchers found that folklore of Tongkat Tunggal Panaluan had many moral massage which could teach children’s character